Vad får domstolen döma över? En studie av värden i svensk straffprocessrätt - Nordstrandh,Per-Emil (2024)
The purpose of this essay is to study the limitations to what the courts can base their judgement on and to analyze the values of the Swedish criminal process. To study the existing limitations to what the court can base their judgements on I have examined the requirements upon the statement of the criminal act as charged set up in chapter 30 section 3 in the code of judicial procedures. To examine the values of the criminal process I have used the two models presented by the American professor of law Herbert L. Packer. His two models, the crime control model and the due process model, are polarities. The crime control model is based on values that the most important function of the criminal process is to repression of criminal activity. The criminal process has the aim to apprehend and convict as many as possible. For that to succeed the criminal process needs to be effective and informal. The other pole is the due process model. The due process model is deeply imprinted by the formal structure of the law. According to the model reliabil-ity is more important than efficiency. The goal of the criminal process is as much to protect the innocent as convict the guilty. Therefore there needs to be safeguards to control that the process is reliable and protecting the innocent. One such safeguard is human rights. The models are made for the American criminal process, and I have therefore adopted the models to work in a Swedish context. I have chosen 24 precedents from the Swedish Supreme court. The cases deal with questions of the statement of the criminal act as charged, other sections than the one the prosecutor has deemed applicable, judicial interference in criminal proceedings and prescription times. I analyze the supreme courts reasoning and conclusions in the precedents. I then place the precedents on the spectrum between the two models. The spectrum used in the essay has three steps, toward the crime control model, in between the two models and toward the due process model. I present my result on the requirements the Supreme court has set up for what the court can base their judgement on. I then conclude that the Swedish Supreme court through its precedents expresses values of both models. In most cases the court expresses values related to the due process model. I end the paper with a reflection regarding how my result affects the criminal process. I discuss the matter of how detailed statement of the criminal act as charged needs to be and how unfortunate expressed reasons in an acquittal can affect the trust in the legal system.
Keywords: straffrätt; straffprocessrätt; criminal law; criminal process; Herbert Packer; due process; crime control; rättssäkerhetsmodellen; brottsbekämpningsmodellen